Implementing Website Design Based on Search Engine Optimization (SEO) Checklist to Increase Web Popularity - Harto, Agus Budi (Swiss German University, 2019)
One way to increase website popularity is by increasing the user's visit to the website. Search Engine Optimization is a popular concept to increase website popularity or page ranking of a website in search engine, but not many designer know on how to implement the concept so their website popularity could not be controlled. This research aims to create a template based on checklist created from SEO concept. Evaluation is done by comparing website page ranking that created based on this checklist and not. The result of this research is the website popularity ranking which implement SEO design is higher.